Electrophysiologic testing for diagnostic evaluation and risk stratification in patients with suspected cardiac sarcoidosis with preserved left and right ventricular systolic function. (23rd July 2019) - Zipse, Matthew M.; Tzou, Wendy S.; Schuller, Joseph L.; Aleong, Ryan G.; Varosy, Paul D.; Tompkins, Christine; Borne, Ryan T.; Tumolo, Alexis Z.; Sandhu, Amneet; Kim, Darlene; Freeman, Andrew M.; Weinberger, Howard D.; et al.
Abstract: Introduction: While cardiac sarcoidosis (CS) carries a risk of ventricular arrhythmias (VAs) and sudden cardiac death (SCD), risk stratification of patients with CS and preserved left ventricular/right ventricular (LV/RV) systolic function remains challenging. We sought to evaluate the role of electrophysiologic testing and programmed electrical stimulation of the ventricle (EPS) in patients with suspected CS with preserved ventricular function. Methods: One hundred twenty consecutive patients with biopsy‐proven extracardiac sarcoidosis and preserved LV/RV systolic function underwent EPS. All patients had either probable CS defined by an abnormal cardiac positron emission tomography or cardiac magnetic resonance imaging, or possible CS with normal advanced imaging but abnormal echocardiogram (ECG), SAECG, Holter, or clinical factors. Patients were followed for 4.5 ± 2.6 years for SCD and VAs. Results: Seven of 120 patients (6%) had inducible ventricular tachycardia (VT) with EPS and received an implantable cardioverter defibrillator (ICD). Three patients (43%) with positive EPS later had ICD therapies for VAs. Kaplan‐Meier analysis stratified by EPS demonstrated a significant difference in freedom from VAs and SCD ( P = 0.009), though this finding was driven entirely by patients within the cohort with probable CS ( P = 0.018, n = 69). One patient with possible CS and negative EPS had unrecognized progression of the disease and unexplained death with evidence of CS at autopsy. Conclusions: EPS is useful in the risk stratification of patients with probable CS with preserved LV and RV function. A positive EPS was associated with VAs. While a negative EPS appeared to confer low risk, close follow‐up is needed as EPS cannot predict fatal VAs related to new cardiac involvement or disease progression.